2020
DOI: 10.1039/c9cp05658k
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene carbonate adsorption on the major surfaces of lithium manganese oxide Li1−xMn2O4spinel (0.000 <x< 0.375): a DFT+U-D3 study

Abstract: Surface reactivity of LiMn2O4 spinel cathode material towards ethylene carbonate (EC) electrolyte solvent using density functional theory (DFT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 76 publications
2
19
0
Order By: Relevance
“…We have used the Vienna Ab initio Simulation Package (VASP) [30][31][32][33] [34,35]. Long-range dispersion interactions were included using the semi-empirical method of Grimme, with the Becke-Johnson damping [D3-(BJ)] [36,37], which is required for the realistic simulation of the bulk and surface properties of several different materials [9,[38][39][40][41][42][43][44][45]. The inner electron included up to the 3s level for Cu; 2p level for Ti; 4f level for Pt; 4s level for Pd and Ag; and 1s level for O, C and N, and were described by the projector augmented wave (PAW) method [46,47], whereas the electron of the H atom was treated as valence.…”
Section: Computationalmentioning
confidence: 99%
“…We have used the Vienna Ab initio Simulation Package (VASP) [30][31][32][33] [34,35]. Long-range dispersion interactions were included using the semi-empirical method of Grimme, with the Becke-Johnson damping [D3-(BJ)] [36,37], which is required for the realistic simulation of the bulk and surface properties of several different materials [9,[38][39][40][41][42][43][44][45]. The inner electron included up to the 3s level for Cu; 2p level for Ti; 4f level for Pt; 4s level for Pd and Ag; and 1s level for O, C and N, and were described by the projector augmented wave (PAW) method [46,47], whereas the electron of the H atom was treated as valence.…”
Section: Computationalmentioning
confidence: 99%
“…The electronic density optimization was stopped when the total energy difference between two consecutive self-consistent loop steps was below 10 –5 eV. In order to accurately describe the long-range dispersion interactions, we have adopted the empirical correction method with the Becke–Johnson damping presented by Grimme and co-workers [D3−(BJ)], , which has been proven reliable in the simulation of surface properties of various materials. , …”
Section: Computational Methodsmentioning
confidence: 99%
“…62−64 Compared to other organic solvents, EC has boiling and melting points, which are approximately 248 and 36.4 °C, respectively. 65 In our previous study, 66 we employed DFT calculations with a Hubbard Hamiltonian and long-range dispersion corrections to study the adsorption of EC onto the low-Miller-index surfaces of LiMn 2 O 4 , where we found that the EC weakly adsorbed on the Mn/Li sites of the spinel surfaces via the carbonyl or ethereal oxygen, thus allowing the molecule to detach easily to expose the (111) surface. However, the reactivity of EC with the coating material α-Al 2 O 3 is equally important but not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found in our previous study, where we investigated the EC adsorption on the major surfaces of the LiMn 2 O 4 spinel. 66 The EC molecule gained small charges of −0.094 and −0.071 e − when it was placed in parallel and perpendicular modes onto the surface. As we increased the surface coverage to θ = 0.50, the charge transfer remained constant in both orientations.…”
Section: Introductionmentioning
confidence: 99%